2020
DOI: 10.1002/app.49655
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved indiffusion behavior of Cu2+ and Ni2+ in polypropylene

Abstract: Microplastics and their effects on the environment and food chain have become increasingly important in recent years. These polymer particles, which are only few millimeters in size or smaller, accumulate in the environment and can enter the human food chain via animals that ingest them. Moreover, they can accumulate impurities such as heavy metals. Therefore, this study focuses on the indiffusion behavior of metal ions into semicrystalline polypropylene (PP) applying time‐of‐flight secondary ion mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, the surface roughness of the polymer layer (200 nm) can also induce this effect due to earlier probing of the lithium signal in thinner coating regions. Kern et al also showed that the metal ion diffusion in polymers is faster in amorphous regions than in crystalline regions . Therefore, the interphase layer shown in Figure c is probably on average thinner and the polymer layer thicker than indicated by the depth profile.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the surface roughness of the polymer layer (200 nm) can also induce this effect due to earlier probing of the lithium signal in thinner coating regions. Kern et al also showed that the metal ion diffusion in polymers is faster in amorphous regions than in crystalline regions . Therefore, the interphase layer shown in Figure c is probably on average thinner and the polymer layer thicker than indicated by the depth profile.…”
Section: Resultsmentioning
confidence: 93%
“…Kern et al also showed that the metal ion diffusion in polymers is faster in amorphous regions than in crystalline regions. 30 Therefore, the interphase layer shown in Figure 3c is probably on average thinner and the polymer layer thicker than indicated by the depth profile. Analyses at different regions of interest showed a decrease of the probable interphase layer of about 50% in areas where the lithium signal is probed later (not shown).…”
Section: Acs Appliedmentioning
confidence: 99%
See 1 more Smart Citation
“… δcδtgoodbreak=δδx][Dδcδx.$$ \frac{\delta c}{\delta t}=\frac{\delta }{\delta x}\left[D\frac{\delta c}{\delta x}\right]. $$ For Sr 2+ diffusion in bovine bone marrow, we assumed diffusion from an exhaustless source into semi‐infinite space as boundary conditions for solving Fick's second law of diffusion (Equation []), as previously described 26,27,53,54 . Following assumptions had to be made 55 : Because species concentration c is proportional to secondary ion intensity I in SIMS, the fit can be carried out with the obtained Sr + ion signal intensities. The measured ion intensity I is considered as a linear function of the real Sr 2+ intensity ( I bg ). Strontium diffusion occurs from an infinite reservoir of Sr 2+ with an intensity I 0 at the initial position x 0 . There are no reactions of Sr 2+ (diffusing species) with the bone marrow matrix. …”
Section: Resultsmentioning
confidence: 99%
“…For Sr 2+ diffusion in bovine bone marrow, we assumed diffusion from an exhaustless source into semi-infinite space as boundary conditions for solving Fick's second law of diffusion (Equation [2]), as previously described. 26,27,53,54 Following assumptions had to be d. There are no reactions of Sr 2+ (diffusing species) with the bone marrow matrix.…”
Section: Determination Of Sr 2+ Diffusion Coefficients In Bovine Bone...mentioning
confidence: 99%